Lepidium colombianum (Lepidieae; Brassicaceae), a new species from South America - Al-Shehbaz, Ihsan A. (Phytotaxa, 2025)
Lepidium colombianum, a new species form Colombia (Cundinamarca Department), is most closely related to L. bipinnatifidum, from which it is readily distinguished by the caducous sepals, glabrous leaves, entire uppermost leaves, and fruiting pedicels puberulent all around.